(untitled) (Veterinary Science, 2017)
The accelerated process of concentration in he Argentine agricultural firms specially affects medium and small productive units. Decapitalization, debts and low productivity prevail nowadays. Different opinions coming from technicians, scientists and firm leaders warn about hazards in firm management. The processing of qualitative information about decision making in agricultural firms in he north of La Pampa province (1995 survey) shows that the majority of managers did not systematize their own firm data, they lacked planning habits and took decisions supported only on mexperience